2001
DOI: 10.1038/sj.bmt.1703138
|View full text |Cite
|
Sign up to set email alerts
|

Life-threatening capillary leak syndrome after G-CSF mobilization and collection of peripheral blood progenitor cells for allogeneic transplantation

Abstract: Summary:We report a case of capillary leak syndrome in a 37-year-old female PBPC donor who received G-CSF 900 g/day for 4 days and underwent leukapheresis. This lady had remained well and stable despite marked leukocytosis during G-CSF treatment, but developed hypotension during leukapheresis, quickly followed by hypoxemia, ascites, pericardial and pleural effusion, shock, edema, neurologic changes and hepatocellular injury. Upon G-CSF withdrawal, dopamine and crystalloid infusion, methylprednisolone treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 5 publications
1
22
0
Order By: Relevance
“…2 The use of G-CSF might increase the release of pro-inflammatory cytokines and enhance this imbalance, which could worsen certain clinical symptoms closely associated with pro-inflammatory cytokines, for example, extravascular volume overload, similar to capillary leak syndrome induced by G-CSF. 16,17 Studies have showed that CY is one of the drugs that can effectively decrease the pro-inflammatory cytokine network. It is reported that combination of CY and prednisone is an effective treatment regimen for patients with POEMS syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…2 The use of G-CSF might increase the release of pro-inflammatory cytokines and enhance this imbalance, which could worsen certain clinical symptoms closely associated with pro-inflammatory cytokines, for example, extravascular volume overload, similar to capillary leak syndrome induced by G-CSF. 16,17 Studies have showed that CY is one of the drugs that can effectively decrease the pro-inflammatory cytokine network. It is reported that combination of CY and prednisone is an effective treatment regimen for patients with POEMS syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The stem cell harvest procedure is more convenient for both donors and medical teams, 1-3 the speed of post-transplant, hematological recovery is faster in recipients, [4][5][6][7] and outcomes are similar compared to that of BMT. [8][9][10] However, there have been occasional reports of mortalities [11][12][13][14][15] and severe complications such as splenic rupture. 16,17 Most of these severe adverse events (SAE) occurred with family donors, appeared as anecdotal or were based on retrospective analyses.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Although cytotoxics are often thought to be important, they are by no means a prerequisite. 20 Most agree that CLS is the result of activation of proinflammatory cytokines. 21 The incident may be higher with GM-SCF than G-CSF.…”
Section: Discussionmentioning
confidence: 99%